2018
DOI: 10.1016/j.apsb.2017.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Correlation analysis between the chemical contents and bioactivity for the quality control of Alismatis Rhizoma

Abstract: In order to clarify regions of production and to discriminate processing methods, quantitative and qualitative analyses for saccharides and terpenes in 35 batches of Alismatis Rhizoma were performed. Methodologies included HPLC—PDA, HPLC—VWD and UHPLC—MSn, combined with principal component analysis (PCA) and partial least squares regression techniques (PLSR). The inhibitory effects of triterpenes and Alismatis Rhizoma extracts on lipase activity were evaluated in vitro. PLSR analysis revealed significant posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Modern chemical structure studies have shown that prostane‐type tetracyclic triterpene is the main form of AR compounds, and the structure primarily has a chain of eight carbons on C 17. The structure mainly includes alisol A, alisol B, alisol C, alisol D and its derivatives. The structure of the derivatives is mostly 11‐deoxy; 16‐epoxy; 13,17‐epoxy; 11/12‐dehydrated; 11‐deoxy‐13,17‐epoxy; 16‐oxo‐11‐deoxy; 16,23‐epoxy.…”
Section: Resultsmentioning
confidence: 99%
“…Modern chemical structure studies have shown that prostane‐type tetracyclic triterpene is the main form of AR compounds, and the structure primarily has a chain of eight carbons on C 17. The structure mainly includes alisol A, alisol B, alisol C, alisol D and its derivatives. The structure of the derivatives is mostly 11‐deoxy; 16‐epoxy; 13,17‐epoxy; 11/12‐dehydrated; 11‐deoxy‐13,17‐epoxy; 16‐oxo‐11‐deoxy; 16,23‐epoxy.…”
Section: Resultsmentioning
confidence: 99%
“…Accurate qualitative and quantitative analysis of target components in TCM is the prerequisites for quality control 7 . Currently, the liquid chromatography–mass spectrometry (LC–MS) 8 , 9 , 10 and gas chromatography−mass spectrometry (GC–MS) 11 are the most popular platforms in pharmaceutical analysis due to best specificity and sensitivity 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The main active ingredients of RA are classified into triterpenoids and sesquiterpenoids [9, 10]. Triterpenoids, such as alisol B 23-acetate, exhibit hypolipidemic, hypoglycaemic, and diuretic effects [2, 6, 7].…”
Section: Introductionmentioning
confidence: 99%